1987
DOI: 10.1515/znc-1987-1-209
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in vitro of Non-Epithelial Intermediate Filament Proteins with Histones

Abstract: Non-epithelial intermediate filament (IF) subunit proteins show a high and specific affinity for core histones at physiological ionic strength. When IF proteins are titrated with a mixture of core histones and linker histone H1, in general the latter is totally excluded from com plexation and in the adducts formed the moderately-arginine-rich histones H2A and H2B are progressively replaced by the very-arginine-rich histones H3 and H4. At histone saturation, 2 molecules of nonneuronal IF protein bind 1 histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…As pointed out previously (Tolstonog et al, 2000), IF proteins are comparable to members of the RAD52 epistasis group and replication protein A, which play an essential role in homologous recombination repair. Conversely, putting its affinity for single-stranded (Traub et al, 1983(Traub et al, , 1992, supercoiled (Kühn et al, 1987), triple-helical, and Z (unpublished observations) DNA as well as for core histones (Traub et al, 1986) into effect, vimentin will certainly also contribute to the marked vulnerability of nuclear matrix-associated DNA to damage by a multitude of noxious physical and chemical agents such as ionizing radiation, UV light, carcinogens, and ROS (reviewed in Boulikas, 1995). Via opening of chromatin structure, vimentin would thus exert opposing effects on the genome: one rendering it more accessible to mutagens and one allowing the invasion of constituents of the recombination/repair machinery at sites of DNA lesions.…”
Section: Vimentin-associated Dna Fragments Have the Characteristics Omentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out previously (Tolstonog et al, 2000), IF proteins are comparable to members of the RAD52 epistasis group and replication protein A, which play an essential role in homologous recombination repair. Conversely, putting its affinity for single-stranded (Traub et al, 1983(Traub et al, , 1992, supercoiled (Kühn et al, 1987), triple-helical, and Z (unpublished observations) DNA as well as for core histones (Traub et al, 1986) into effect, vimentin will certainly also contribute to the marked vulnerability of nuclear matrix-associated DNA to damage by a multitude of noxious physical and chemical agents such as ionizing radiation, UV light, carcinogens, and ROS (reviewed in Boulikas, 1995). Via opening of chromatin structure, vimentin would thus exert opposing effects on the genome: one rendering it more accessible to mutagens and one allowing the invasion of constituents of the recombination/repair machinery at sites of DNA lesions.…”
Section: Vimentin-associated Dna Fragments Have the Characteristics Omentioning
confidence: 99%
“…On the basis of these observations and the strong affinity of vimentin for repetitive and mobile DNA sequences, especially if these elements are, in addition, under superhelical tension (Kühn et al, 1987), it has been proposed that vimentin also plays a role in recombination processes (Tolstonog et al, 2000), which take place, for instance, during cell immortalization or cell senescence (Macieira-Coelho, 1996; see also accompanying paper in this issue). As a DNA-binding protein with an additional strong and selective reactivity with core histones (Traub et al, 1986), vimentin may mediate these processes by acting as a chromatin-modifying scaffold protein.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the cIF proteins may make use of their high affinities in vitro for such nuclear constituents as the lamin B component of the nuclear lamina Djabali et al, 1991;Bastos et al, 1992), DNAs and RNAs Vorgias and Traub, 1986;Tolstonog et al, 2000;Q. Wang et al, 2001), and histones (Traub et al, 1987b). That the affinity binding of type III IF proteins to a large variety of repetitive and mobile, recombinogenic DNA sequences (X.…”
Section: Introduction C Ytoplasmic Intermediate Filaments (Cifs) Havementioning
confidence: 99%
“…Among the crossconnected DNA fragments, centromeric and telomeric DNA were the most prominent, in addition to micro-and minisatellites and transposable sequence elements of the LINE, SINE and A-type particle families. The specificity of the cIF protein-histone interactions emerged from the exclusion of linker histone H1 from complex formation as long as core histones were present in small excess, the preferential affinity of the filament proteins for the arginine-rich histone species H3 and H4, and the stoichiometry of the adducts, with 16 core histone molecules bound to each cIF protein tetramer (Traub et al, 1987b).…”
Section: Introduction C Ytoplasmic Intermediate Filaments (Cifs) Havementioning
confidence: 99%
“…Critically important to the interpretation and conclusions of this study are the data obtained from control experiments: the organization of the nuclei of cells lacking vimentin remains unaffected by treatment with HIV-1 PR. Because the limit digest of vimentin by HIV-1 PR produces a mixture of several peptides (Shoeman et al, 1990a,b), corresponding roughly to the head domain, the rod domain and the tail domain, and because it has been shown that the various domains of vimentin can interact with themselves and some other related proteins (Traub et al, 1992b;Meng et al, 1996) as well as with histones (Traub et al, 1986), it was of interest to define which peptide(s) of this mixture was responsible for the changes observed. The amino-terminal peptide NT1 was originally chosen because it was available in sufficient quantity and purity, is almost identical to the largest amino-terminal peptide produced by HIV-1 PR, and because it encompasses a domain of vimentin known to be involved in interactions with a variety of compounds, including nucleic acids, lipids, and coiled-coil protein structures (Traub et al, 1992b and references therein).…”
mentioning
confidence: 99%